1993
DOI: 10.1182/blood.v81.7.1726.1726
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stroma in humans: anti-nerve growth factor receptor antibodies selectively stain reticular cells in vivo and in vitro

Abstract: Two anti-nerve growth factor receptor (LNGFR or p75NGFR) antibodies, Me20.4 and Me8211, label stromal cells with dendritic features in fresh smears and in formalin-fixed, paraffin-embedded human bone marrow (BM). The LNGFR+ cells have an oval nucleus, a scanty cytoplasm with long dendrites that intermingle with the hematopoietic cells, line the abluminal side of sinus endothelial cells, and provide the scaffold for the hematopoietic marrow. At the electron microscopy level, the immunogold tag labels the body a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 48 publications
3
55
1
Order By: Relevance
“…Our findings corroborate previous reports demonstrating that BMSCs isolated from healthy donors express BDNF high affinity receptor TrkB, indicating that paracrine BDNF signaling in the marrow microenvironment may occur. ( 16–18 ) The data suggested that the addition of BDNF can stimulate VEGF secretion by BMSC, and this effect can be blocked by K252α, which is an specific inhibitor of TrkB. We further detected VEGF secretion by MM cell lines and BMSCs isolated from healthy donors.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our findings corroborate previous reports demonstrating that BMSCs isolated from healthy donors express BDNF high affinity receptor TrkB, indicating that paracrine BDNF signaling in the marrow microenvironment may occur. ( 16–18 ) The data suggested that the addition of BDNF can stimulate VEGF secretion by BMSC, and this effect can be blocked by K252α, which is an specific inhibitor of TrkB. We further detected VEGF secretion by MM cell lines and BMSCs isolated from healthy donors.…”
Section: Discussionmentioning
confidence: 85%
“…Besides its frequent expression by malignant plasma cells, TrkB was found to be expressed by osteoblasts, endothelial cells, and BMSCs in the BM microenvironment. ( 16–18 ) Since BDNF and its receptor TrkB expressed by MM cells contribute to plasma cell survival, TrkB expressed by BMSCs may allow stroma–myeloma cell interaction, further influencing BM angiogenesis via secreting angiogenic cytokines. In addition, studies of our group found that the increased serum BDNF levels detected in patients with MM correlated with disease activity and serum VEGF levels.…”
mentioning
confidence: 99%
“…The bone marrow stromal microenvironment is composed of cells, structural fibrils and extracellular matrix (‘ground substance’). The cellular components include macrophages, fibroblastic cells (including several types of adventitial and reticular cells), adipocytes and endothelial cells, as well as other less well characterized cells (Weiss & Chen, 1975; Watanabe, 1985; Cattoretti et al , 1993). The most common structural fibrils in the bone marrow are collagen, reticulin, laminin and fibronectin (Bentley et al , 1981; Reilly et al , 1985; Cattoretti et al , 1993).…”
Section: Bone Marrow Microenvironmentmentioning
confidence: 99%
“…Although CD15, CD33, CD34, and CD13 are known to be the most common antigens expressed in M1 patients (Foon and Todd, 1986), there are reports describing the expression of CD13 on various non‐hematopoietic cells, including epithelial cells from renal proximal tubules and intestinal brush border, endothelial cells, fibroblasts, brain cells, and bone MSC (Look et al, 1986). Furthermore, detailed immuno‐EM characterization of human bone MSC revealed the expression of CD13 as well as the nerve growth factor receptor (NGFR), alkaline phosphatase, reticulin, collagen III, and vimentin (Cattoretti et al, 1993). In this study, the high expression of CD13 in AML‐I cells does not exclude the possibility of a myeloid cell origin for AML‐I cells, but a defect in the expression of other leukemia‐associated antigens strongly support the idea of a mesenchymal origin for AML‐I cells rather than a hematopoietic origin.…”
Section: Discussionmentioning
confidence: 99%